Implementasi Pembelajaran Kitab Al-Arobiyah Bayna Yadaika dalam Meningkatkan Pemahaman Mahasiswa - Ahmad Taufiq; Inayah Priyatun (Qismul Arab: Journal of Arabic Education, 2022)
Language is considered very important by people and even by the world because it is considered a necessity as well as dependence in capturing the understanding of what the interlocutor is saying. In Indonesia, there are three languages ??that are very popular and often used in life, especially in the world of education. The first language is Indonesian as communication, and two foreign languages, namely English and Arabic as the language to be studied for the future. Therefore, it takes an Arabic language learning in the first step to get to know and apply Arabic in everyday life, both in terms of profession or just for personal needs. This research is descriptive, qualitative, which means a research conducted to get an overview or description of the Arabic language, regarding learning Arabic through the Kitab al-Arobiyah Bayna Yadaika by a number of IAIN Pekalongan students who reside in the An-Nur Dormitory, Pekalongan Regency. This learning is considered to have been able to build the enthusiasm and activeness of students. This is evidenced by the preparation of students when they will follow the course of learning.